(untitled) (Archives of Criminology, 2006)
The patterns of justice existing in the former Soviet Union have endured in most Soviet successor states despite the collapse of the USSR. Rather, the Soviet legacy in the criminal justice arena has been much more enduring than many observers had suggested. Although the last year and a half has seen the Rose, Orange and Kyrgyz revolutions, major change in the legal system has been less profound than in many former socialist countries of Eastern Europe. These revolutions represented popular revolts against the corruption of the ruling elite but they have not brought systemic justice reforms. Georgia may have experienced the most profound effort to promote justice reform, but the reform is not in all sectors of the legal system. Ukraine, despite the change in the national leadership, has yet to make major reforms in its legal system. Russia, in many ways returning to its Soviet patterns of behaviour, has a justice system subject to the political desires of the national leadership. Unlike in many countries, in Eastern Europe where there has been a motivation to join the European Union and to leave behind the Soviet legacy, the successor states to the USSR still face legal systems as corrupted, inefficient and authoritarian as those tied to the Marxist-Leninist system. The problems of the justice system remain even without a Communist ideology. Without a political will to change these systems, a new legal consciousness among the citizenry or a strong incentive for change, the situation in the Slavic states of the former USSR resembles in profound ways the system that was supposedly left behind. The last year and a half has seen three "so-called" revolutions in Soviet successor states – Georgia, Ukraine and Kyrgyzstan. But in only one of these has there been an effort to introduce profound change into the legal system and to right the wrongs committed during the previous government. Even though there have been many lessons learned from this experience, a government that is well-intentioned but not wise in govemance cannot resolve the serious challenges to order in a highly criminalised and corrupt society. The Soviet legacy combined with the pre-revolutionary authoritarian traditions are proving more intractable to reform than many anticipated.